Management of Giant Thoracic Disc Herniation by Thoracoscopic Approach: Experience of 53 Cases. Issue 6 (17th October 2018) - Brauge, David; Horodyckid, Catherine; Arrighi, Marta; Reina, Vincent; Eap, Christophe; Mireau, Etienne; Bertrand, Baussart; Aldéa, Sorin; Gaillard, Stephan
Abstract: BACKGROUND: Giant thoracic disc herniation (gTDH) is a rare condition. It is defined by a herniation that occupies at least 40% of the thoracic spinal canal and is usually calcified. Several surgical techniques have been described to date but this surgery remains a technically difficult procedure. OBJECTIVE: To report the long-term outcome of 53 patients with myelopathy due to gTDH who were operated on by a thoracoscopic approach. The technical details of the preoperative assessment and the surgical procedure are presented. METHOD: We present a retrospective study of a database of 53 patients operated for symptomatic gTDH by a thoracoscopic approach. The following clinical parameters were assessed initially and used during follow-up: Frankel grade and JOA score adapted to the thoracic spine (mJOA), pain in the lower limbs and limitation of the walking perimeter to less than 500 meters. The quality of spinal cord decompression was assessed postoperatively by magnet resonance imaging (MRI). RESULTS: The mean follow-up was 78.1 mo (SD 49.4). At the last follow-up visit, clinical examination showed a mean improvement of 0.91 Frankel grade ( P  < 0.001) and 2.56 mJOA score respectively ( P  < 0.001). Lower limb pain and walking perimeter were also improved. Postoperative MRI revealed that the resection was complete in 35 cases, subtotal in 13 cases, and incomplete in 5 cases. CONCLUSION: gTDH is a condition that often evolves favorably after surgery. The thoracoscopic approach is a feasible alternative technique.